The Technology of Scientific Сreativity in the Professional Training of the Music Teacher - Akbarova, Gulnaz; Dyganova, Elena; Shirieva, Nadezda; Adamyan, Anna (Journal of History Culture and Art Research, 2018)
New realities of the modern educational space make it necessary to equip future music teachers with technologies of scientific creativity based on independent research activity. Having identified the problem areas, the authors propose the solution to the systemic organization of the independent research activity of the student subject to the specificity of musical and pedagogical education in accordance with the requests of the society. During the research, pedagogical possibilities of independent research and creative work of the student were revealed; the characteristics of the steps in the format of "Written abstract to the vocal-choral composition" are presented; a set of pedagogical support was developed in the form of a teaching aid and a diagnostic technique for determining the level of professionally required results of a music teacher. The theoretical substantiation of the diagnostic function of the written annotation for the vocal-choral product allowed expanding the scientific understanding of the functional of such types of scientific research works. The introduction of author’s developments into the educational process has allowed to obtain convincing results: the understanding by the future teacher of music of the relationship between mastering the methods of scientific knowledge and technology of scientific creativity with personal and professional values and interests; increase of the level of development of the research competence of a musician student; formation of experience of scientific-research and research-creative activity of the future music teacher; increase in the level of formation of a culture of self-education of a teacher of music; and theoretical and practical readiness of future musicians for professional self-actualization in the conditions of real practice.